Effect of Different Sizes and Heights on the Removal Efficiency of Composite Clay Filter for Gold Mine Site Wastewater Remediation - Olatunji, Abass Adekunle; Ayanshola, Ayanniyi Mufutau; Ajala, Mary Adejoke; Erhuanga, Ebelechukwu (Tecno Scientifica Publishing, 2024)
Wastewater from mining-related activities contains toxic elements that require remediation, and most available wastewater filters have inconsistent flow rates and removal efficiency due to their thickness. This study, therefore, examined the effect of height and size on the flow rate and removal efficiency of a clay composite filter for wastewater remediation. The developed clay filter and its composites were characterized using various techniques such as X-ray fluorescence (XRF), X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR). The XRF analysis showed that the clay contained 91.38% major minerals, including iron oxide (Fe2O3), aluminum oxide (Al2O3), and silica (SiO2), which could enhance the filtration process. Additionally, FTIR revealed that both the clay and the filter are rich in functional groups, including kaolinite and illite, which could promote the filtration process. Further analysis showed that the filters had an average adsorption rate of 87.32%, an average flow rate of 0.891 L/hr, and an average removal efficiency of 99.6%. An increase in the height of a small-diameter filter resulted in a 0.21% increase in removal efficiency, while for larger diameters, the removal efficiency decreased by 0.11%. Conversely, increasing the diameter of a short filter increased the efficiency by 0.25%, while for taller filters, the removal efficiency decreased by 0.07%. Therefore, this work demonstrated that both height and diameter have noticeable effects on flow rate: as height increases, flow rate decreases, and as diameter increases, flow rate increases. The filter's efficiency is somewhat affected by both height and diameter, with a small increase in efficiency noted at greater heights and a slight decrease in efficiency noted at larger diameters.